THE EFFECT OF ACCOUNTING CONSERVATISM, EARNINGS MANAGEMENT AND DEBT MATURITY ON COMPANY FINANCIAL PERFORMANCE - Fitriani, Azizah (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
ABSTRACT It seeks to find "the influence of accounting conservatism, earnings management, and debt maturity on company financial performance." Study participants are real estate property companies listed on the Indonesia Stock Exchange from 2018 to 2022. Researchers used purposive sampling. The study covered 17 firms. The Conservatism Accounting variable has a greater tcount value of 2.567 compared to the ttable value of 1.989 (or 0.012 < 0.05). Profit Management Variable, with -2.501 > ttable = -1.989 or 0.014 < 0.05, suggests a partial correlation between Accounting Conservatism and Financial Performance. Profit Management affects Financial Performance less. Debt Variable Maturity is -1.018 with ttable = -1.989 and 0.312 > 0.05. If debt maturity somewhat affects financial performance, the accounting conservatism (X1), profit management (X2), and debt maturity (X3) regression model on financial performance (Y) is valid or plausible. A contemporaneous impact is indicated by a Sig of 0.004, below 0.05.